2021
DOI: 10.1002/fsn3.2614
|View full text |Cite
|
Sign up to set email alerts
|

Superfruits in China: Bioactive phytochemicals and their potential health benefits – A Review

Abstract: It is widely known that nutrient intake is the most important mean of maintaining health and preventing diseases. Since the use of some synthetic antioxidants has been restricted for their possible toxic and carcinogenic effects (Yen et al., 1998), food containing natural antioxidants gained worldwide popularity. Nutritional studies paid much attention to vegetables and fruits for their roles in alleviating the risk of numerous non-communicable diseases (Shahidi & Ambigaipalan, 2015). Regular consumption of fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 86 publications
0
8
0
Order By: Relevance
“…Previous studies have found that these physiologically active ingredients play a significant role in the healthy functions of soymilk and other soy foods, and can prevent a variety of chronic diseases, including cardiovascular diseases, insulin resistance, breast cancer, and immune dysregulation (3). In recent years, with the rise of plant-based foods (4)(5)(6), fermented soymilk has attracted extensive attention because of its nutritionally and physiologically active components changes and its consequent enhanced health effects during fermentation (7)(8)(9)(10). Fermented soymilk prepared using special Lactobacillus fermentum obtained from Xinjiang yak yogurt, Chongqing kimchi and Taiwan fermented cabbage, such as LP-HFY01, CQPC08, and TWK10, exhibited good free radical scavenging effect (11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have found that these physiologically active ingredients play a significant role in the healthy functions of soymilk and other soy foods, and can prevent a variety of chronic diseases, including cardiovascular diseases, insulin resistance, breast cancer, and immune dysregulation (3). In recent years, with the rise of plant-based foods (4)(5)(6), fermented soymilk has attracted extensive attention because of its nutritionally and physiologically active components changes and its consequent enhanced health effects during fermentation (7)(8)(9)(10). Fermented soymilk prepared using special Lactobacillus fermentum obtained from Xinjiang yak yogurt, Chongqing kimchi and Taiwan fermented cabbage, such as LP-HFY01, CQPC08, and TWK10, exhibited good free radical scavenging effect (11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…Rosa roxburghii fruits have drawn much attention due to their high abundance of bioactive compounds, such as polyphenols, superoxide dismutase, polysaccharide, vitamin C, and vitamin E [ 16 ]. Water-soluble polysaccharide extract from Rosa roxburghii fruits has demonstrated the potential to be a hypoglycemic agent [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is a highly valuable plant in terms of the content of varied substances of high nutritional value Kubczak et al, 2022). Parts of the plant such as seeds, fruits and leaves contain polyunsaturated fatty acids, organic acids, amino acids, flavonoids, catechins, proanthocyanidins, carotenoids, vitamins C, E, P, A, B group, phytosterols and tocopherols as well as mineral elements (potassium, phosphorus, calcium, magnesium, iron, zinc, manganese, copper, cadmium) (Liu et al, 2021;Ren et al, 2020;Sławińska et al, 2023a;Wang et al, 2022). Table 1 shows selected biologically active ingredients.…”
Section: Chemical Compositionmentioning
confidence: 99%